"I Just Started Writing": Toward Addressing Invisibility, Silence, and Mortality Among Academically High-Achieving Black Male Secondary Students. (November 2016) - Everett, Sakeena
Many Black male students in our nation's schools feel like teachers do not see them for who they are or who they hope to become. In an academic enrichment writing course, high-achieving Black male secondary students utilized metaphor to imagine new realities for themselves. This article examines a Black male student's narrative writing to capture how he made meaning of his own writing across academic settings as he transitioned from high school to college. The author argues metaphor functioned as a powerful catalyst for understanding how he constructed, embodied, and negotiated his racialized and gendered schooling experiences. In doing so, the author offers metaphor as an important entry point, theoretical framework, and pedagogical tool to promote substantial writing experiences for Black male students in academic spaces. This empirical research is intentional in honoring student voice—a perspective often void in research, yet invaluable in preparing teachers to work more effectively with this population.